2009 First International Communication Systems and Networks and Workshops 2009
DOI: 10.1109/comsnets.2009.4808884
|View full text |Cite
|
Sign up to set email alerts
|

Trie partitioning in distributed PC based routers

Abstract: Abstract-Recent research in PC based routers has proposed a distributed architecture. Such an architecture poses several challenges in the areas of scalability, robustness, efficiency of routing, latency and other issues. We examine the issue of decrease in throughput due to large routing tables in this architecture and propose partitioning as a solution. Our contribution is twofold: defining the concept of load for a node in a forwarding table trie and to show by simulation experiments the effectiveness of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Routebricks [9] defines an architecture that parallelizes the packet forwarding functionality across multiple PCs and across multiple cores of the CPUs within each PC. A technique to improve performance of a distributed OSR was studied in [2]. Thus considerable research effort has been devoted to analyzing and improving the performance of OSRs in both a single PC and in distributed configurations.…”
Section: A Linux Open Software Routersmentioning
confidence: 99%
See 2 more Smart Citations
“…Routebricks [9] defines an architecture that parallelizes the packet forwarding functionality across multiple PCs and across multiple cores of the CPUs within each PC. A technique to improve performance of a distributed OSR was studied in [2]. Thus considerable research effort has been devoted to analyzing and improving the performance of OSRs in both a single PC and in distributed configurations.…”
Section: A Linux Open Software Routersmentioning
confidence: 99%
“…However, implementing WFQ in a distributed system such as the STSDR has several challenges. In our STSDR implementation, we observed that a lot of computing power was left over after implementing basic routing functionality [2], [11]. Hence we choose to implement WFQ to take advantage of the available computing capacity in the STSDR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation